2008
DOI: 10.2307/25470679
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and Structural Diversification of the Larval Nervous System Among Marine Bryozoans

Abstract: Abstract. Regardless of the morphological divergence among larval forms of marine bryozoans, the larval nervous system and its major effector organs (musculature and ciliary fields) are largely molded on the basis of functional demands of feeding, ciliary propulsion, phototactic behaviors, and substrate exploration. Previously published ultrastructural information and immunohistochemical reconstructions presented here indicate that neuronal pathways are largely ipsilateral, with more complex synaptic connectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 55 publications
3
60
0
Order By: Relevance
“…Pires and Woollacott (1997) and Shimizu et al (2000) reported brieXy on distribution of serotonin in larvae of Bugula neritina. Further data on coronate larvae have been obtained from Triphyllozoon mucronatum (Wanninger et al 2005b) and Celleporaria sherryae (Santagata 2008). The only immunocytochemical data from cyphonautes larvae come from Membranipora sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pires and Woollacott (1997) and Shimizu et al (2000) reported brieXy on distribution of serotonin in larvae of Bugula neritina. Further data on coronate larvae have been obtained from Triphyllozoon mucronatum (Wanninger et al 2005b) and Celleporaria sherryae (Santagata 2008). The only immunocytochemical data from cyphonautes larvae come from Membranipora sp.…”
Section: Introductionmentioning
confidence: 99%
“…The only immunocytochemical data from cyphonautes larvae come from Membranipora sp. (Hay-Schmidt 2000) and Membranipora membranacea (Santagata 2008). However, bryozoans exhibit several more diVerent larval types.…”
Section: Introductionmentioning
confidence: 99%
“…The cell types and anatomy of the larval nervous system and musculature have been better studied in selected species of gymnolaemates, and, collectively, these data support some broad-scale homology with the larval neuromuscular systems of spiralian protostomes (Santagata 2008b ;Gruhl 2009 ;Wanninger 2009 ) All gymnolaemate embryos have a late gastrula stage with a comparatively large ring of coronal cells equatorially arranged between the more cell-rich oral and aboral larval fi elds. In species with a cyphonautes larva, the entirety of the oral cell fi eld will be internalized as the embryo fl attens laterally and takes on a more trapezoidal shape (Fig.…”
Section: Late Developmentmentioning
confidence: 58%
“…In all species investigated, these cells form the larval pyriform complex consisting of a superior and an inferior glandular fi eld of cells bordering four specialized multiciliated cells that constitute the vibratile plume. The pyriform complex has numerous other sensory and neuronal cells (Reed et al 1988 ;Santagata 2008b ) used during crawling behaviors to probe various substrates before metamorphosis. Another derivative of this cell tier is the oral epithelium that consists of ciliated cells whose primary function is to capture food particles (the ciliated ridges and cell lining of the vestibule) in feeding larvae.…”
Section: Early Developmentmentioning
confidence: 99%
See 1 more Smart Citation